Weed interference in Marandu palisade grass pastures under renewal or maintenance conditions - de Marchi, Sidnei R.; Marques, Ricardo F. [UNESP]; Araújo, Prissila P. Dos S.; Silva, Ilgner T. D.; Martins, Dagoberto [UNESP] (FapUNIFESP (SciELO), 2022)
The presence of weeds as a consequence of pasture degradation is one of the main problems facing livestock worldwide. Thus, knowing the interference aspects and the appropriate time for weed management is essential for applying a particular control measure. This research aimed to study the weed interference on the morphostructural and nutritional quality of the Marandu palisade grass in conditions of renewal or maintenance of pasture. The experiments were conducted in a randomized block design, with four replicates and treatments consisted of eight growth periods of coexistence between Marandu palisade grass and weeds (0, 15, 30, 45, 60, 75, 90, and 120 days). Forage grass was characterized at the end of the experimental period, corresponding to 120 days of coexistence, and the main morphostructural and nutritional components were determined. Under the renewal or maintenance process, the weeds interfere in the morphostructural and nutritional quality of pasture areas with Marandu palisade grass. In vitro organic matter digestibility of Marandu palisade grass is negatively influenced by weeds, suggesting that control measures for renewal or maintenance areas should be adopted within 24 and 18 days of coexistence, respectively.
Interferência de plantas daninhas em pastagens de capim Marandu sob condições de renovação ou manutenção
Keywords: Brachiaria brizantha; In vitro digestibility; Indigestible fibers; Pasture degradation